2019
DOI: 10.3390/ijms20020454
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 and HDAC2 Double Knockout Triggers Cell Apoptosis in Advanced Thyroid Cancer

Abstract: Anaplastic thyroid carcinoma (ATC) and squamous thyroid carcinoma (STC) are both rare and advanced thyroid malignancies with a very poor prognosis and an average median survival time of 5 months and less than 20% of affected patients are alive 1 year after diagnosis. The clinical management of both ATC and STC is very similar because they are not particularly responsive to radiotherapy and chemotherapy. This inspired us to explore a novel and effective clinically approved therapy for ATC treatment. Histone dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…In the current study, we found that cytotrophoblasts expressed HDAC1 and HDAC2, and that knockdown of either HDAC1 or HDAC2 did not impact syncytiotrophoblast formation. Interestingly, in cells with reduced HDAC1 or HDAC2, we observed increased expression of the paralogous protein, which is consistent with results in other studies 40,49,50 . However, inhibition of both HDAC1 and HDAC2 using FK228, or knockdown of both HDAC1 and HDAC2, inhibited cytotrophoblast differentiation, suggesting that HDAC1 and HDAC2 can compensate for each other during syncytiotrophoblast development.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we found that cytotrophoblasts expressed HDAC1 and HDAC2, and that knockdown of either HDAC1 or HDAC2 did not impact syncytiotrophoblast formation. Interestingly, in cells with reduced HDAC1 or HDAC2, we observed increased expression of the paralogous protein, which is consistent with results in other studies 40,49,50 . However, inhibition of both HDAC1 and HDAC2 using FK228, or knockdown of both HDAC1 and HDAC2, inhibited cytotrophoblast differentiation, suggesting that HDAC1 and HDAC2 can compensate for each other during syncytiotrophoblast development.…”
Section: Discussionsupporting
confidence: 92%
“…Class I-specific HDACi 4SC-202 globally increases both of H3K27ac and H3K4me3 levels around the TSS of genes, but notably decreases occupancy at proximal regions of TSS of genes such as SMAD family member 6 (SMAD6) and E2F transcription factor 8 (E2F8), which are associated with enhancer deactivation (Mishra et al, 2017). Panobinostat and Jamaladdin et al, 2014Heideman et al, 2013Lin et al, 2019Haberland et al, 2009Boucheron et al, 2014Preglej et al, 2020Montgomery et al, 2007Moresi et al, 2012;Dovey et al, Montgomery et al, 2008Lu et al, 2018Ho et al, 2020Bhaskara et al, 2008Bhaskara et al, 2010;Jiang and Hsieh, 2014Ji et al, 2019Hsu et al, 2015Phelps et al, 2016 Chen Impairs genome stability; embryonic lethality Vaquero et al, 2007;Wang et al, 2008 Represses angiogenesis Potente et al, 2007;Dioum et al, 2009;Lim et al, 2010 Impairs nicotinamide mononucleotide (NMN)-induced amelioration of liver fibrosis and NMN-dependent telomere integrity in premature aging mice Amano et al, 2019 Causes methionine restriction-induced lethality in mouse ESC Tang S. et al, 2017 Impairs myeloid-derived suppressor cells (MDSC) differentiation by disturbing glycolytic pathway Liu et al, 2014 Impairs various DNA repair Cohen et al, 2004;Yuan et al, 2007;Ming et al, 2010;Meng et al, 2020 Inhibits autophagy in MEFs Lee et al, 2008 Causes differentiation defects of mice ESC Tang Induces abnormal mitochondrial physiology, oxidative stress and genomic instability Kim et al, 2010 R...…”
Section: Transcription Modulatorsmentioning
confidence: 99%
“…However, when the combined effect of valproic acid and paclitaxel was compared with paclitaxel alone in a phase II/III clinical trial no advantage was found [29]. Pan HDAC inhibitor panobinostat is an FDA approved drug in third line against multiple myeloma and it also has a strong cytotoxic effect in ATC and squamous thyroid carcinoma cells through induction cell cycle arrest and apoptosis [30,31].…”
Section: Introductionmentioning
confidence: 99%